William Shakespeare and Modern English: To What Extent the Influence of Him in Modern English - Devilito P. Tatipang (Journal of English Language Teaching, Literature and Culture, 2022)
Shakespeare’s works at that time considered a work of high art. The influence of his work has been a source of inspiration for many artists to create paintings, operas and ballet performances. Studying Shakespeare is like studying life from multiple perspectives: psychological, political, philosophical, social, spiritual. The rhythms he uses in his words are reflected in the rhythms of our bodies. Known as the greatest English-language writer in history, and earning him the nickname of England's national poet, William Shakespeare is the author with the most-played theatrical work to date. More than four centuries since his death, William Shakespeare is still one of the greatest English playwrights. The tens of thousands of people who throng to see Shakespeare's plays will be able to hear the 1700 words created by Shakespeare. Many of his words are currently in use. Examples: "deafening" (deaf)," hush", "hurry" (quickly), " downstairs" (below), " gloomy" (sad), " lonely" (alone), "embrace" (hugs), " dawn" (twilight). The spelling used by Shakespeare was different from his time. Elizabethans spelled words as they were written, such as Latin and Indonesian. There is no "correct" way to spell. People write a word the way they want it to be spelled.